2019
DOI: 10.1186/s12916-019-1341-6
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-infiltrating lymphocytes signature predicts survival in patients with early/intermediate stage hepatocellular carcinoma

Abstract: Background Intratumoral immune infiltrates have manifested a robust prognostic signature in patients with hepatocellular carcinoma (HCC). We hypothesized that a novel tissue-related immune signature (TRIS) could improve the prediction of postoperative survival for patients diagnosed with early/intermediate HCC. Methods Twenty-eight immune features were immunohistochemically examined on 352 HCC specimens. The LASSO Cox regression model was used to construct a five-featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 56 publications
(74 reference statements)
0
28
0
Order By: Relevance
“…Tissue microarray (TMA) construction was performed as previously described . Briefly, two representative areas with infiltrating lymphocytes were selected on H&E‐stained slides.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue microarray (TMA) construction was performed as previously described . Briefly, two representative areas with infiltrating lymphocytes were selected on H&E‐stained slides.…”
Section: Methodsmentioning
confidence: 99%
“…Duplicate cores (2 μm in diameter) were taken, arrayed and re–embedded from tumor and peritumor regions. Fourteen monoclonal and two polyclonal antibodies against CD3, CD4, CD8, CD14, CD20, CD27, CD45RO, CD45RA, CD57, CD66b, CD68, CD103, Foxp3, CXCR5, PD‐L1 and PD1 were used for staining, as reported previously . To evaluate peritumoral and intratumoral infiltrating immune cells, the three most representative and independent fields were selected and photographed at ×200 magnification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LASSO Cox analysis, as a wildly used high-dimensional predictor regression method (18), selecting the optimal penalty parameter lambda using 10-fold cross-validations to prevent overfitting (19), can achieve shrinkage and variable identify simultaneously (20), and thus, which is an appropriate solution to establish signatures if there are numerous correlated covariates (21). Therefore, we utilized LASSO Cox regression analysis in the training set to establish an IIRPSS by a linear combination of selected prognostic cell compositions among 22 immune cell types weighted by the optimal coefficients.…”
Section: Construction An Immune Infiltration-related Prognostic Scorimentioning
confidence: 99%
“…An international multi-nation corporation of 14 centers assessed the the immunoscore based on the amounts of CD3+ and CD8+ T cells in TNM stage I-III colon cancer, and finally proved that the immunoscore provided the highest relative contribution to the risk of recurrence in colon cancer. 13 The proposal and effectiveness of the immunoscore has been validated in several other cancers such as gastric cancer, 14 hepatocellular carcinoma 15 , urothelial carcinoma of the bladder 16 and so on. These existing evidence indicated that immunoscore provides a more accurate prognosis.…”
Section: Introductionmentioning
confidence: 99%